INDEKS KEMAMPUAN PROSES BERDASARKAN PROPORSI PERSESUAIAN UNTUK DISTRIBUSI NON NORMAL - Lakmi Prita Wardhani; Resty Z Fahrida; Nur Hasanah (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2010)
This paper discusses about graph labeling. We will nd edge magic total labeling of cycle and expanding cycle graph. In the nal, we investigate the critical set of edge magic total labeling on cycle and expanding cycle graph.